PENGARUH BULLYING TERHADAP MINAT BELAJAR SISWA SMAN 1 KAMPAR TIMUR - Lestari, Indah Puji; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
This research is motivated by an emerging phenomenon, namely bullying on student interest in SMAN 1 Kampar Timur, where there are forms of bullying that occur in SMAN 1 Kampar Timur and the effect of bullying on student interest in SMAN 1 Kampar Timur, based on Based on this background, the problem of this research can be formulated as to whether the dominant form of bullying occurs in SMAN 1 Kampar Timur and whether there is an effect of bullying on student interest in SMAN 1 Kampar Timur. This study aims to determine the dominant form of bullying that occurs in SMAN 1 Kampar Timur and to examine the effect of bullying on student interest in SMAN 1 Kampar Timur. The type of research used is descriptive quantitative with the measuring tools used for each variable are questionnaires and interviews. The population used in this study was 1.095 students and a sample of 110 students of class XI SMAN 1 Kampar Timur with purposive sampling technique. The scoring uses a Likert scale for each question item with two types of scales, namely the scale of bullying behavior and interest in learning. Data analysis using SPSS Version 16.0 application assistance. Based on the calculation results of the SPSS version 16.0 application, the F test obtained the value of Ftableâ‰¤Fcount, namely 1.197â‰¤3.08 so that H0 is accepted and Ha is rejected, which means that bullying has no significant effect on student interest in learning at SMAN 1 Kampar Timur. While the coefficient of determination (R Square) of 0.011 indicates that the effect of bullying on interest in learning is only 1.1% and 98.9% is another factor that affects student interest in learning besides bullying at school. This means that the hypothesis in this study is rejected.Key Words: Influence, Bullying, Student Interest In Learning.